Evaluation of Three Fixation Methods in Tibiotalocalcaneal Fusion for Chronic Osteomyelitis Following Ankle Fracture - Laura C. Gaitan; Emanuel Gonzalez; Juan Pablo Randolino; Valeria López; Gastón Slullitel (Foot & Ankle Orthopaedics)
Category: Ankle; Other Introduction/Purpose: In the context of chronic osteomyelitis following an ankle fracture, limb salvage through treatment—ideally including infection eradication—can be an alternative to amputation. Tibiotalocalcaneal arthrodesis is perhaps the most popular procedure, widely familiar among surgeons. When performing fusion in osteomyelitis patients, external fixation is more commonly used, although there is some experience with internal fixation systems. In this study, we conducted a retrospective evaluation of three groups of consecutively treated patients undergoing tibiotalocalcaneal fusion using either circular or monoplanar external fixation or an endomedullary nail coated with antibiotic-loaded cement. Our objective was to assess the success of each procedure in terms of consolidation, infection remission, and improvement in the quality of life. Methods: A multicenter, retrospective, descriptive study of 17 patients treated with tibiotalocalcaneal fusion, divided into three groups based on the treatment performed: Group A used a retrograde endomedullary nail coated with Polymethylmethacrylate (PMMA) with antibiotic, Group B used a monoplanar LRS (Limb Reconstruction System) external fixator, and Group C used a circular external fixator; all with a minimum follow-up of 12 months. Quality and the percentage of consolidation were evaluated through tomography. Additionally, the SF-12 form was administered to assess the quality of life at the last follow-up visit. Results: 17 patients were evaluated. Group A: 6 patients stabilized with a coated nail. Average tibiotalar and subtalar consolidation rates were 66.24% and 67.06%. One patient did not achieve infection healing. SF-12 scores averaged 40 for physical and 48.13 for mental. Group B: 5 patients with an LRS fixator; 3 active smokers. Average tibiotalar and subtalar consolidation rates were 52.78% and 62.3%, respectively. All patients achieved infection remission. SF-12 scores averaged 46.7 for physical and 51.3 for mental. Group C: 6 patients stabilized with a circular external fixator; 1 diabetic and 3 were smokers. Average tibiotalar and subtalar consolidation rates were 65.9% and 65.7%. Half experienced infection recurrence. SF-12 scores averaged 36.7 for physical and 47.8 for mental. Conclusion: Patients with retrograde nails coated with PMMA and antibiotics exhibit higher consolidation rates than the rest; however, patients with circular external fixation had a higher infection recurrence rate. Establishing generalizable treatment algorithms for these patients remains challenging, but our data suggest a favorable trend toward the use of internal endomedullary fixation coated with PMMA.